DESCRIPTION AND ANTHROPOMETRIC COMPARISON APPLIED TO MOTION IN TAEKWONDOINES (Fiep Bulletin - online, 2020)
Objective: To determine in analysis, the description and comparison of anthropometry applied to movement in taekwondo practitioners.Materials and methods: It is a descriptive correlational study, within a quantitative framework, where the sample was intended with a number of variables evaluated were obtained through anthropometric criteria and physical muscular power of the lower train. The study was carried out during the first half of 2019-1Results: With reference to the levels of explosive force 89.7%, it presents a range in average power, in the same way the elastic index (IE), shows that 48.3%, shows contractile muscular deficit, only 44, 8%, shows the use of accumulated elastic energy, followed by the rate of use of arms (IUB), 72.4, uses the use of arms, while 13.8% has a contractile deficit.Conclusions: According to the conclusion of the objectives, the correlation was verified under statistical analysis, through systematic work, consequently the results yielded a significant negative correlation (higher fat less jump) and a significant positive Correlation (greater muscle mass jump). Consequently, the limits of this research are of a particular order, however, its methodology can be extrapolated in other similar study groups in quantitative work.
Keywords: anthropometry; body composition; adipose tissue